Analysis of horizontal milling machine vibration on the influence of gear module cutters with sizes M1 and M1.5 - Zaira, Jupri Yanda; Haiqal, Muhammad; Sitinjak, Bherry Arif; Prasetyo, Yoga Ali; Hasibuan, Muhammad Refky; Alhabib, Fauzan; Sinaga, Indra; Hardyanto, Rio (Applied Engineering and Technology, 2024)
This study examines the effect of vibrations on the horizontal milling machine type 1216 during gear manufacturing using cutter modules with diameters of 50 mm and 55.25 mm, each at a cutting depth of 1 mm. Displacement, velocity, and acceleration measurements were conducted in vertical, horizontal, and axial directions using a VM-6370 vibration meter, with the average vibration amplitudes analyzed. The results revealed that the 55.25 mm cutter produced the highest vibration amplitude in the horizontal direction, reaching 353.270 mm/sÂ², while the lowest was in the vertical direction at 171.293 mm/sÂ². For the 50 mm cutter, the highest amplitude occurred in the vertical direction at 0.1336 mm and the lowest in the horizontal direction at 0.0583 mm. These findings demonstrate that larger cutter modules generate higher vibration amplitudes, significantly affecting the precision and surface quality of gear manufacturing. The study emphasizes the importance of selecting appropriate cutter sizes to minimize vibrations, optimize manufacturing processes, and improve product quality. By providing a detailed analysis of the relationship between cutter size and vibration levels, this research is a valuable reference for enhancing the efficiency and accuracy of gear cutting in industrial applications.